2001
DOI: 10.1074/jbc.m101751200
|View full text |Cite
|
Sign up to set email alerts
|

The Profibrinolytic Enzyme Subtilisin NAT Purified fromBacillus subtilis Cleaves and Inactivates Plasminogen Activator Inhibitor Type 1

Abstract: In this report, we demonstrate an interaction between subtilisin NAT (formerly designated BSP, or nattokinase), a profibrinolytic serine proteinase from Bacillus subtilis, and plasminogen activator inhibitor 1 (PAI-1). Subtilisin NAT was purified to homogeneity (molecular mass, 27.7 kDa) from a saline extract of B. subtilis (natto). Subtilisin NAT appeared to cleave active recombinant prokaryotic PAI-1 (rpPAI-1) into low molecular weight fragments. Matrix-assisted laser desorption/ionization in combination wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
102
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(106 citation statements)
references
References 42 publications
1
102
0
3
Order By: Relevance
“…(54); (v) the enzyme subtilisin NAT purified from Bacillus subtilis (55). However, in these approaches the concept of destabilizing the complex between VN and PAI-1 was hardly considered.…”
Section: Discussionmentioning
confidence: 99%
“…(54); (v) the enzyme subtilisin NAT purified from Bacillus subtilis (55). However, in these approaches the concept of destabilizing the complex between VN and PAI-1 was hardly considered.…”
Section: Discussionmentioning
confidence: 99%
“…(Suzuki et al, 2003) found that dietary supplementation of Natto suppressed intimal thickening and modulated the lysis of mural thrombi after endothelial injury in rat femoral artery. Furthermore, NK can cleave active recombinant prokaryotic plasminogen activator inhibitor into low molecular weight fragments (Urano et al, 2001). Those researches imply that NK is useful as a promising thrombolytic agent (Sumi et al,1990).…”
Section: Introductionmentioning
confidence: 97%
“…Similarly, the role of PAI-1 in bacterial pathogenesis is also supported by the increased level of the plasminogen inhibitor during sepsis and other severe pathological conditions [21][22][23]. Some bacterial pathogens such as Pseudomonas aeruginosa, Staphylococcus aureus, and Bacillus subtilis cause degradation of PAI-1 during invasion [24][25][26]. Bacterial proteases also degrade Vn during invasion [27,28], but there is no information available on degradation of the PAI-1/Vn complex.…”
Section: The Pai-i/vn Complex and Bacterial Pathogenesismentioning
confidence: 99%